2014
DOI: 10.3389/fmicb.2014.00423
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur source-mediated transcriptional regulation of the rhlABC genes involved in biosurfactants production by Pseudomonas sp. strain AK6U

Abstract: Despite the nutritional significance of sulfur, its influence on biosurfactants production has not been sufficiently studied. We investigated the expression of key biosurfactants production genes, rhlABC, in cultures of Pseudomonas sp. AK6U grown with inorganic or organic sulfur sources. AK6U grew with either inorganic sulfate (MgSO4), dibenzothiophene (DBT), or DBT-sulfone as a sole sulfur source in the presence of glucose as a carbon source. The AK6U cultures produced variable amounts of biosurfactants depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 37 publications
2
26
1
Order By: Relevance
“…Moreover, in line with our results, it has been reported that rhamnolipid composition depends on many factors such as the producing strain, culture conditions, and medium composition [27], [29]. The higher proportion of di-rhamnolipids as compared to mono-rhamnolipids (in the DBT and DBT-sulfone cultures) is in a good agreement with the previously reported higher expression level of the rhlC gene compared to the rhlB gene [21]. Furthermore, the predominance of the di-rhamnolipid L-Rha–L-Rha–C 10 –C 10 congener in all the analyzed cultures agrees with data reported in the literature [40].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, in line with our results, it has been reported that rhamnolipid composition depends on many factors such as the producing strain, culture conditions, and medium composition [27], [29]. The higher proportion of di-rhamnolipids as compared to mono-rhamnolipids (in the DBT and DBT-sulfone cultures) is in a good agreement with the previously reported higher expression level of the rhlC gene compared to the rhlB gene [21]. Furthermore, the predominance of the di-rhamnolipid L-Rha–L-Rha–C 10 –C 10 congener in all the analyzed cultures agrees with data reported in the literature [40].…”
Section: Discussionsupporting
confidence: 92%
“…Such qualitative and quantitative differences were exhibited in the rhamnolipid congeners produced in cultures containing organosulfur (DBT, DBT-sulfone) and inorganic sulfur substrates. The variations in rhamnolipid congener profiles reflect the recently reported differences in the rhlABC gene expression among the DBT, DBT-sulfone, and inorganic sulfate cultures [21]. Moreover, in line with our results, it has been reported that rhamnolipid composition depends on many factors such as the producing strain, culture conditions, and medium composition [27], [29].…”
Section: Discussionsupporting
confidence: 91%
“…This mosaic nature of AK6 is expected to fit better than axenic monocultures for the development of biotechnological processes targeting desulfurization of a broad range of sulfur compounds present in crude oil and diesel. Furthermore, deployment of mixed cultures may prevent the decay of the biodesulfurization activity resulting from the accumulation of the inhibitory intermediates of the 4S pathway [37,42].In fact, all detected 16S rRNA gene sequences are related to those of bacterial genera that are known as biodesulfurization-competent, hydrocarbon degraders, or inhabitants of hydrocarbons-polluted environments [43,44].…”
Section: Biodesulfurization Capabilities Of a Mixed Culturementioning
confidence: 99%
“…Not only the less-researched strains and classes but a significant leap is required investigating the carbon sources that would work best for high biosurfactant production. Addressing this area are the original research articles by Antoniou et al ( 2015 ), Gudiña et al ( 2015 ) and Ismail et al ( 2014 ), and a review by Banat et al ( 2014 ).…”
mentioning
confidence: 99%
“…strain AK6U greatly varies depending on the sulfur source. They showed that a biosurfactant yield of 1.3 g/l was obtained in presence of dibenzothiophene (DBT) as a carbon source which was higher than obtained in presence of DBT-sulfone (0.5 g/l) and the inorganic sulfate (0.44 g/l) (Ismail et al, 2014 ). To bring together these types of “carbon-source” based studies for “low-cost” biosurfactant production technologies Ibrahim M. Banat and co-authors wrote an intensive review where they discussed how and why despite so many developments on biosurfactants their commercialization remain difficult, costly and to a large extent irregular and what role does the low-cost renewable raw substrates and fermentation technology play in reducing the overall production cost.…”
mentioning
confidence: 99%